The division of wrongs a historical comparative study - Descheemaeker, Eric, 1977- (Oxford : Oxford University Press, 2009)
Civilian law, in contrast to common law, structures its law of wrongs according to degree of blameworthiness. This text explores the history of this structure from Roman law to modern French law, and argues that adopting such a division would clarify confusions in the common law of torts.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Torts -- History; Civil law systems; Roman law; Civil law -- France -- History; Common law -- History; Common law -- Roman influences